Dynamic instability of lithiated phosphorene. Issue 53 (1st September 2020) - Jia, Lingchun; Yuan, Hongchun; Chang, Yingli; Gu, Mu; Zhu, Jiajie
Abstract : Introduction of C improves transition capacity between intercalation and conversion reactions for multilayer phosphorene. Abstract : Li-ion batteries are widely used energy storage units. Although phosphorene delivers a high Li capacity, the transition capacity between the intercalation reaction and the conversion reaction is still not clear. We investigate the structural and electronic properties of Li intercalated phosphorene and graphene/phosphorene/graphene sandwiches by first-principles calculations. The competition to obtain charge from Li between C and P reduces charge depletion on the interlayer P–P bonds, improving stability. Importantly, the sandwiches show higher transition capacities than freestanding phosphorene, confirmed by ab initio molecular dynamics simulations. The trilayer structures show better structural reversibility than the monolayers.